2003
DOI: 10.1002/dev.10149
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in eyeblink conditioning and simple spike activity in the cerebellar cortex

Abstract: The activity of neurons in the cerebellum exhibits learning-related changes during eyeblink conditioning in adult mammals. The induction and preservation of learning-related changes in cerebellar neuronal activity in developing rats may be affected by the level of maturity in cerebellar feedback to its brainstem afferents, including the inferior olive. Developmental changes in cerebellar plasticity were examined by recording the activity of Purkinje cells in eye regions of cerebellar cortical lobule HVI (lobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
(96 reference statements)
1
19
1
Order By: Relevance
“…The developmental changes in pontine neuronal activity correspond to developmental changes in CS-elicited neuronal activity in the cerebellar cortex and nuclei Nicholson and Freeman Jr. 2004). As a result of CS pathway development, CS input to the cerebellum in younger rats may not be strong enough to induce synaptic plasticity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The developmental changes in pontine neuronal activity correspond to developmental changes in CS-elicited neuronal activity in the cerebellar cortex and nuclei Nicholson and Freeman Jr. 2004). As a result of CS pathway development, CS input to the cerebellum in younger rats may not be strong enough to induce synaptic plasticity.…”
Section: Discussionmentioning
confidence: 96%
“…The most substantial developmental change in the US pathway is an increase in the magnitude of cerebellar inhibitory feedback to the inferior olive (Nicholson and Freeman Jr. 2003a,b). The developmental change in inhibitory feedback is due to an increase in inhibitory synapses within the inferior olive (Nicholson and Freeman Jr. 2003a). Developmental addition of inhibitory synapses within the inferior olive results in a decrease in complex spike activity in the cerebellar cortex, which influences the maintenance of synaptic plasticity within the cerebellum.…”
mentioning
confidence: 99%
“…Studies of Pkj firing during trace eyeblink conditioning paradigms have shown both simple monophasic and complex, multiphasic changes in spike output during conditioned stimuli (25,26). These complex changes may be partially due to the mechanisms described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Simple spikes were recorded using the same experimental techniques as the Freeman and Nicholson (2000) study. Stimulus-evoked and learning-related modulation of Purkinje cell simple spike activity from eye regions within lobule HVI emerged ontogenetically in parallel with eyeblink conditioning (Nicholson & Freeman, 2004). During paired CS-US training, the proportion of simple spikes that showed learning-specific increases or decreases in activity increased with age.…”
Section: Development Of Cerebellar Learning Mechanismsmentioning
confidence: 91%
“…In addition to developmental changes in the frequency and magnitude of learning-specific neuronal activity in the cerebellum, there was a substantial developmental increase in the magnitude of neuronal responses to the CS and US Nicholson & Freeman, 2004). The ontogenetic increase in the cerebellar response to the US suggests that the neural pathway that conducts US stimulation to the cerebellum or the synaptic connections between the US pathway and cerebellar neurons undergoes substantial developmental change postnatally.…”
Section: Us Pathway Developmentmentioning
confidence: 99%